2016
DOI: 10.1111/clr.12938
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and radiographic parameters around short (6 to 8 mm in length) and long (11 mm in length) dental implants placed in patients with and without type 2 diabetes mellitus: 3‐year follow‐up results

Abstract: Short implants can demonstrate clinical and radiographic stability in a manner similar to conventional long implants in patients with and without T2DM. The role of oral hygiene and glycemic maintenance in this scenario cannot be disregarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
3
17
0
1
Order By: Relevance
“…Similarly, these parameters were comparable in T2DM and prediabetes patients. These results are based on the findings proposed by previous studies …”
Section: Discussionsupporting
confidence: 70%
“…Similarly, these parameters were comparable in T2DM and prediabetes patients. These results are based on the findings proposed by previous studies …”
Section: Discussionsupporting
confidence: 70%
“…3 In order to circumvent these invasive surgical procedures, short implants, which are 6 to 8 mm in length were developed. 3,4 Clinical studies [3][4][5] have shown that short implants can exhibit clinical and radiographic stability in a manner similar to standard 10 mm long implants. Moreover, in a 14-year follow-up longitudinal clinical study, 6 the survival rates of standard-length and short dental implants were similar, 97.1% and 97.9%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when glycemic levels are strictly maintained (by medications and/or dietary control), dental implants can osseointegrate and remain functionally stable in diabetic subjects in a way comparable with systemically healthy individuals . There is abundant evidence in indexed literature that has shown that implants can demonstrate survival rates of 100% among patients with well‐controlled diabetes . It is therefore recommended that hyperglycemic patients, such as those with prediabetes and diabetes mellitus undergoing dental implant therapy should be encouraged to regularly monitor and maintain glycemic levels within normal ranges.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 There is abundant evidence in indexed literature that has shown that implants can demonstrate survival rates of 100% among patients with well-controlled diabetes. [25][26][27][28] It is therefore recommended that hyperglycemic patients, such as those with prediabetes and diabetes mellitus undergoing dental implant therapy should be encouraged to regularly monitor and maintain glycemic levels within normal ranges. This may help attain long-term stability of dental implants and improved overall health status in these individuals.…”
Section: Discussionmentioning
confidence: 99%